2018
DOI: 10.3389/fpsyg.2018.00839
|View full text |Cite
|
Sign up to set email alerts
|

Selfie Expectancies Among Adolescents: Construction and Validation of an Instrument to Assess Expectancies Toward Selfies Among Boys and Girls

Abstract: Selfie-taking and posting is one of the most popular activities among teenagers, an important part of online self-presentation that is related to identity issues and peer relations. The scholarly literature emphasizes different yet conflicting motivations for selfie-behavior, stressing deeper analysis of psychological factors and the influence of gender and age. Expectancies are “explanatory device[s]” that can help us study adolescent behavior. However, no instruments have been devised that specifically explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 58 publications
(89 reference statements)
4
57
1
3
Order By: Relevance
“…These findings appeared in line with several previous studies that found a strong association between females' engagement in social media use and depressive mood, low self-esteem, and other psychological distress, leading to their greater problematic social networking (McCrae et al, 2017;Nowland et al, 2018;Raudsepp and Kais, 2019). However, the negative outcomes due to problematic social networking appeared to affect more boys than girls, likely due to males' higher attention for sexual aspects of online body image-related activities and engagement in online sexual behaviors (Jonsson et al, 2014;Bianchi et al, 2018;Boursier and Manna, 2018b) and/or due to a higher online disinhibition (Casale et al, 2015) despite other studies finding that females were more engaged in online self-disclosure (Schouten et al, 2007). No statistically significant difference between girls' and boys' preferences for online social interactions was found.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These findings appeared in line with several previous studies that found a strong association between females' engagement in social media use and depressive mood, low self-esteem, and other psychological distress, leading to their greater problematic social networking (McCrae et al, 2017;Nowland et al, 2018;Raudsepp and Kais, 2019). However, the negative outcomes due to problematic social networking appeared to affect more boys than girls, likely due to males' higher attention for sexual aspects of online body image-related activities and engagement in online sexual behaviors (Jonsson et al, 2014;Bianchi et al, 2018;Boursier and Manna, 2018b) and/or due to a higher online disinhibition (Casale et al, 2015) despite other studies finding that females were more engaged in online self-disclosure (Schouten et al, 2007). No statistically significant difference between girls' and boys' preferences for online social interactions was found.…”
Section: Discussionsupporting
confidence: 88%
“…However, in accordance with previous findings (Griffiths et al, 2014;Andreassen et al, 2017;Boursier and Manna, 2019), the present study also showed higher engagement by girls relating to time spent on SNSs and BICP, investing more time than boys in creating selfportraits as a way to express their identity and to manage own positive and negative images, promoting their best selfpresentation and applying privacy restrictions to moderate relational exchanges via photos. On the contrary, boys used greater body image control to improve their sexual attractiveness, confirming the males' great attention for sexual aspects of online body images that might promote sexual exploration experiences (Boursier and Manna, 2018b). Moreover, in terms of problematic social networking, female adolescents were significantly more likely than males to use SNSs to regulate their mood states, with higher cognitive preoccupation and poorly self-regulated SNS use.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…From a clinical point of view, the use of diachronic narrative devices that can promote the expression, sharing and containment of emotions (Boursier and Manna, 2018; Dicé et al, 2019; Margherita et al, 2017; Tessitore and Margherita, 2017), especially the negative ones, starting from the diagnosis (T1), may help maintain psychological adjustment in the face of the disease during the different phases of treatment (Martino et al, 2019). Furthermore, actively processing and expressing emotions enhance the adjustment and health status of patients with breast cancer (Weihs et al, 2008), and poor EP predicts more rapid disease progression (Reynolds et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular relevance to the present study, existent studies show that women tend to take more selfies than men [3,[49][50][51] and feel worse after engaging in appearance-related comparisons [50]. However, according to Liziliziduanxin [52], there is a growing number of males using photo-beautification apps, which may be representative of males' facial concerns.…”
Section: Considerations About Gendermentioning
confidence: 85%